Acute Respiratory Distress Syndrome: Mortality in a Single Center According to Different Definitions - Santa Cruz, Roberto; Veronica Alvarez, Lic; Heredia, Roberto; Villarejo, Fernando (My University, 2017)
Background: Mortality in acute lung injury (ALI) remains high, with outcome data arising mostly from multicenter studies. We undertook this investigation to determine hospital mortality in patients with ALI in a single center. Methods: We studied patients admitted between 2005 and 2012 with ALI and acute respiratory distress syndrome (ARDS) according to the American European Consensus Conference (AECC) criteria and recorded clinical variables. Thereafter, patients were classified as subgroups according to the AECC and Berlin definition in order to compare the clinical characteristics and outcomes. Results: In the 93 patients comprising the study, hospital mortality was 38%. Mortality at 28 days was 36%. Multivariate analysis associated hospital mortality with age and Pao(2)/Fio (2) on day 1 (P < .001). Differences resulted between the subgroups of AECC (ALI vs ARDS) and Berlin (mild vs moderate vs severe ARDS) in the lung injury score, Pao(2)/Fio(2), Pao(2)/P(A)o(2), PaCo2 on day 1, and hospital mortality. Conclusion: The overall hospital mortality (38%) was similar to that of other studies and according to the presence of ARDS (Pao(2)/Fio(2) <= 200), we found significant differences between ALI and ARDS (AECC) and between mild and moderate or severe ARDS (Berlin) in baseline respiratory variables and mortality.
Keywords: outcomes; respiratory failure; intensive care; epidemiology